2007
DOI: 10.1016/j.wsif.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Muslim women's new defenders: Women's rights, nationalism and Islamophobia in contemporary Australia

Abstract: In recent years, Australian nationalism has been increasingly framed against a dangerous Muslim 'other'. This paper offers a gendered analysis of this nationalism, arguing that a discourse of protecting women's rights has enabled Islam to be portrayed as inherently misogynistic and therefore a threat to Australia's egalitarian culture. This racialised paternalism was clearly articulated in debates surrounding the December 2005 Cronulla riots, a response to the alleged aggressive and misogynistic behaviour of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 6 publications
1
71
1
Order By: Relevance
“…Muslims are more likely to be stopped and searched for security reasons, and more likely to be tried in the courts (Poynting & Perry, 2007). Consequently, media and governmental policies have contributed to the rising rates of Islamophobia, which is present in the form of unfounded fears, and prejudicial and stereotypical thinking (Bouma, 2011;Dunn et al, 2007;Ho, 2007;Kabir, 2007). There is an element of "us versus them" thinking on the behalf of non-Muslim Australians, which is tarnishing the social inclusivity and harmony in Australia (Ata, 2015;Hopkins, 2011;Poynting & Mason, 2006).…”
Section: Acculturative Stressmentioning
confidence: 99%
“…Muslims are more likely to be stopped and searched for security reasons, and more likely to be tried in the courts (Poynting & Perry, 2007). Consequently, media and governmental policies have contributed to the rising rates of Islamophobia, which is present in the form of unfounded fears, and prejudicial and stereotypical thinking (Bouma, 2011;Dunn et al, 2007;Ho, 2007;Kabir, 2007). There is an element of "us versus them" thinking on the behalf of non-Muslim Australians, which is tarnishing the social inclusivity and harmony in Australia (Ata, 2015;Hopkins, 2011;Poynting & Mason, 2006).…”
Section: Acculturative Stressmentioning
confidence: 99%
“…Another common critique is summed up in the question, 'who needs cross cultural dialogue? ' (Jones 1993, Ho 2007. The question reminds us that those who are marginalised do not need workshops in order to learn about the workings of the 'mainstream', and the benefits of conversations across difference often reflect the needs and desires of the privileged more than the priorities of those who are subjected to prejudice.…”
Section: The Limits Of Storytellingmentioning
confidence: 99%
“…To the extent that Human Libraries confine their aims and strategies to changing personal attitudes through one-on-one conversation, the projects are and will remain typical of a shift in contemporary funded antiracism work which has seen the focus move from questions of access and equity to an increasing focus on dialogue and social inclusion. The early years of the 'war on terror' saw an upsurge in interest and funding for interfaith dialogue as the preferred antiracism strategy, alongside a decline in funding for strategies whereby institutions seek to address racism within (Ho 2007). Human Libraries can be seen as a more generalised strategy with similar aims but a broader focus, beyond relationships between Muslim and non-Muslim Australians.…”
Section: Connecting With Wider Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…In research on Muslim women and the media and on Muslim women's networks, the organisers found a need for 'safe spaces' to discuss issues of gender, race and religion, as women's rights had been 'hijacked' in public debate (Ho 2007) and Muslim women struggled to be heard on their own terms in the media (Dreher 2003(Dreher , 2006.…”
mentioning
confidence: 99%